Improving Luttinger-liquid plasmons in carbon nanotubes by chemical doping. Issue 14 (26th March 2018) - Tian, Xiaoling; Gu, Qingyuan; Duan, Jiahua; Chen, Runkun; Liu, Huaping; Hou, Yanxue; Chen, Jianing
Abstract : We increased the charge carrier density in semiconducting single-walled carbon nanotubes (s-SWCNTs) by HNO3 doping and achieved real-space imaging of plasmons in s-SWCNTs. Abstract : We realized the real-space imaging of Luttinger-liquid plasmons in semiconducting single-walled carbon nanotubes (s-SWCNTs) and studied the effects of chemical-doping-induced charge carrier density modulation on plasmons. Using scattering-type scanning near-field optical microscopy (s-SNOM), we compared the Luttinger-liquid plasmonic behavior in pre- and post-HNO3 -doped SWCNTs. Raman measurements revealed that the physical mechanism is P-type doping. Through HNO3 doping, we effectively increased the charge carrier density in s-SWCNTs and achieved quantum plasmons simultaneously with strong confinement ( λ 0 / λ p ≈ 70) and high quality factor ( Q ≈ 20). The combination of high quality factor and strong subwavelength confinement in Luttinger-liquid plasmons is critical to the future application of plasmonic devices.